Clinical Research of Combined Intravenous Administration and Topical Application of Tranexamic Acid to a Surgical Wound During Posterior Lumbar Fusion. (April 2018) - Ou, Yufu; Wei, Jianxun; Li, Rongzhu; Liang, Bin; Qiu, Dezan; Wei, Minke; Mu, Xiaoping; Li, Zhuhai
Background. The safety and effectiveness of combined intravenous and topical administration of tranexamic acid (TXA) on the reduction of blood loss in patients undergoing posterior lumbar fusion are not yet clear. The study aimed to investigate the safety and effectiveness of the combined intravenous and topical administration of TXA on the reduction of blood loss in patients undergoing posterior lumbar fusion. Method. One hundred and eighteen patients who underwent double-segment posterior lumbar decompression and fusion from February 2014 to May 2016 in our hospital were retrospectively reviewed. Patients were divided into two groups, the experimental group and the control group. Preoperative demographics, operative parameters, and adverse effect were recorded and compared. Results. Intraoperative blood loss, postoperative 24-hour drainage volume, and blood transfusion ratio and volume were significantly lower in the experimental group than in the control group (P < .01); on postoperative 24 hours and 48 hours, hemoglobin and hematocrit levels were significantly higher in the experimental group than in the control group (P < .01). Prothrombin time and fibrinogen content were not significantly different between the 2 groups. The postoperative length of hospital stay was shorter in the experimental group than in the control group (P < .01). No postoperative thrombotic events were reported in either group. Conclusions. Combined intravenous and topical administration of TXA seems to be effective and safe in reducing allogenic blood transfusion and blood loss in double-segment posterior lumbar decompression and fusion surgery.